Discovery of novel, potent and orally efficacious inhibitor of neutral amino acid transporter B0AT1 (SLC6A19). (1st December 2021) - Desai, Jigar; Patel, Bhaumin; Darji, Brijesh; Gite, Archana; Panchal, Nandini; Bhosale, Gokul; Shedage, Sandeep; Patel, Sandip; Kadam, Pravin; Patel, Gautam; Kumar Srivastava, Brijesh; Joharapurkar, Amit; et al.
Graphical abstract: Highlights: Inhibition of neutral amino acid transporter B 0 AT1 (SLC6A19) activity has been recently identified as promising strategy to treat type 2 diabetes and related disorders. Pharmacological inhibition of B 0 AT1 known to stimulate GLP1 and FGF21 in mice. This paper describes our efforts to discover first in class nanomolar potent B 0 AT1 inhibitor with excellent pharmacokinetics in mice. We have demonstrated animal efficacy data of lead B 0 AT1 inhibitor in diet induced obese (DIO) mice model. Abstract: Amino acid restriction by inhibition of neutral amino acid transporter, B 0 AT1 (SLC6A19) activity has been recently shown to improve glyceamic control by upregulating glucagon like peptide (GLP1) and fibroblast growth factor (FGF21) in mice. Hence, pharmacological inhibition of B 0 AT1 is expected to treat type-2 diabetes and related disorder. In this study, rationally designed trifluoromethyl sulfonyl derivatives were identified as novel, potent and orally bioavailable B 0 AT1 inhibitors. Compound 39 was found to be nanomolar potent (IC50 : 0.035 µM) B 0 AT1 inhibitor with excellent pharmacokinetic profile (%F: 66) in mice and efficacious in vivo in diet induced obese (DIO) mice model.